Impact of Procalcitonin Guidance on Management of Adults Hospitalized with COPD Exacerbations. (4th October 2017) - Bremmer, Derek; DiSilvio, Briana; Hammer, Crystal; Beg, Moeezullah; Vishwanathan, Swati; Speredelozzi, Daniel; Moffa, Matthew; Hu, Kurt; Abdulmassih, Rasha; Makadia, Jina; Sandhu, Rikinder; Naddour, Mouhib; et al.
Abstract: Background: Antibiotics are often prescribed for hospitalized patients with chronic obstructive pulmonary disease (COPD) exacerbations. The use of procalcitonin (PCT) in the management of pneumonia has safely reduced antibiotic durations, but there remains limited data on the impact of PCT guidance on the management of COPD exacerbations. Methods: A retrospective, pre-intervention/post-intervention study was conducted to compare the management of patients admitted with COPD exacerbations before and after implementation of PCT guidance at two teaching hospitals in Pittsburgh, Pennsylvania. The pre-intervention period was 3/1/2014–10/31/2014, and the post-intervention period was 3/1/2015–10/31/2015. The primary outcome was duration of antibiotic therapy for COPD. Secondary objectives included duration of IV antibiotics, duration of inpatient length of stay (LOS), and 30-day readmission rates. Results: There were no differences in mean age (66.2 vs 65.9; P = 0.82) or use of home oxygenation (65% vs 61%; P = 0.67) in the pre-intervention and post-intervention groups, respectively. Primary and secondary outcomes can be seen in Table 1. In the post-intervention group, 16/139 (11.5%) patients had an elevated PCT  (> 0.25 µg/L). Patients with an elevated PCT received longer durations of antibiotics compared with those with low PCT levels (5.3 vs 2.7; P = 0.001). Conclusion: Utilizing PCT guidance in the management of COPD exacerbations decreased both the total duration of antibiotic therapy and hospital LOS without negatively impacting hospital readmissions. Disclosures: All authors: No reported disclosures.